Anticipatory approach to war and agenda building: a content analysis study of Portuguese press coverage of the Ukraine war (2014–2023) - Espírito Santo, Paula (Frontiers in Political Science, 2024)
This study, grounded in an anticipatory approach and viewed from an agenda-building perspective, explores the role of the press as a key player, especially in the context of the Russia–Ukraine war. The central research question is: how can communication and the press play a role during war to break a reactive response cycle? The anticipatory approach has proven highly valuable in many fields, especially when addressing the urgency of several policy domains that require greater evidence and research. Communication, particularly the role of the press during a war, can be seen as the final layer perceived directly by the population. The agenda-building approach has been key in understanding news-making processes. From an anticipatory perspective, analyzing media coverage allows for the examination of the inter-influence between policymakers, decision-making outcomes, and various social and media agents. Methodologically, this study applies the content-analysis technique to a selection of Portuguese newspapers (daily and weekly) covering the period from 2014 to 2023. The criteria for selecting news articles included those providing political and strategic information regarding the Ukraine war, with references to international organizations, European Union actors, and Russian and Ukrainian actors. The expected results aim to provide empirical evidence of the relationship between different regimes and how policymakers and political processes are dynamically positioned for future actions, considering the role of the press.